Fatwa as a legal and religious tool: Between State Authority and Scholarly Independence (Al Basirah, 2025)
The fatwa, is a non-binding and flexible Islamic ruling, issued by a qualified and expert Muslim jurist. Historically, the domain of issuing fatwa was in the hand of scholarly individuals who served to respond all queries posed by the public over issues like family matters, economic transactions, ethical matters and international relations. With the advent of modern nation-states, where the need of issuing institutionalized fatwa has been sought, the procedure of issuing fatwa has undergone very significant transformation, especially in the contemporary modern world from the hands of individuals into the domain of institutions. Experiences of Egypt’s Dar al-Ifta, Saudi Arabia’s Council of highly Senior Scholars, and Indonesia’s Majelis Ulama Indonesia (MUI) are the major examples where practice of fatwa is in the hand of institutions weather controlled by the state authority or function as semi-state agency, instead of being in the hands of individual scholars. Though this model has many benefits as to harmonize interpretation of religious texts with the national interests and also to counter extremism yet it also raises concerns regarding the politicization of the religious process and authority as well as damages the scholarly independent role in Islamic jurisprudence. In the case of Pakistan where institutions are not fully controlled by the state authority to issue fatwa rather they act as advisory nature and provide Islamic interpretation over matters posed by the public also dār ul iftās and individuals are issuing fatwas where confusion and conflict may arises between religious context and state interest as evident from the case studies explained in the article. So whether the fatwa issuing authority should remain in the hands of individuals or it should be shifted under the state monitoring, is the question of this article. Previously written material reflects only on the authority of the religious scholars where a comparative analysis between state and independent scholars on the status of fatwa and its impact on the society is not found. Through comparative analysis this article tries to address this issue. It suggests a hybrid system of issuing fatwa by individual scholars in issues related to public matters, but in matters where state policy, interest and integrity involved the stakeholders must be consulted wherein.
Keywords: Fatwa; Mufti; state authority; Islamic Law; religious institutions; hybrid approach in fatwa